Brain sparing effect in growth‐restricted fetuses is associated with decreased cardiac acceleration and deceleration capacities: a case–control study. (23rd September 2015) - Stampalija, T; Casati, D; Monasta, L; Sassi, R; Rivolta, MW; Muggiasca, ML; Bauer, A; Ferrazzi, E
Abstract : Objective: Phase rectified signal averaging (PRSA) is a new method of fetal heart rate variability (fHRV) analysis that quantifies the average acceleration (AC) and deceleration capacity (DC) of the heart. The aim of this study was to evaluate AC and DC of fHR [recorded by trans‐abdominal fetal electrocardiogram (ta‐fECG)] in relation to Doppler velocimetry characteristics of intrauterine growth restriction (IUGR). Design: Prospective case–control study. Setting: Single third referral centre. Population: IUGR ( n = 66) between 25 and 40 gestational weeks and uncomplicated pregnancies ( n = 79). Methods: In IUGR the nearest ta‐fECG monitoring to delivery was used for PRSA analysis and Doppler velocimetry parameters obtained within 48 hours. AC and DC were computed at s = T = 9. The relation was evaluated between either AC or DC and Doppler velocimetry parameters adjusting for gestational age at monitoring, as well as the association between either AC or DC and IUGR with or without brain sparing. Results: In IUGRs there was a significant association between either AC and DC and middle cerebral artery pulsatility index (PI; P = 0.01; P = 0.005), but the same was not true for uterine or umbilical artery PI ( P > 0.05). Both IUGR fetuses with and without brain sparing had lower AC and DC than controls, but this association was stronger for IUGRs with brain sparing. Conclusions: Our study observed for the first time that AC and DC at PRSA analysis are associated with middle cerebral artery PI, but not with uterine or umbilical artery PI, and that there is a significant decrease of AC and DC in association with brain sparing in IUGR fetuses from 25 weeks of gestation to term. Tweetable abstract: Brain sparing in IUGR fetuses is associated with decreased acceleration and deceleration capacities of the heart. Tweetable abstract: Brain sparing in IUGR fetuses is associated with decreased acceleration and deceleration capacities of the heart.